Nutritional Deficiencies of Clarified White Grape Juices and Their Correction in Relation to Fermentation - Houtman, A.C.; du Plessis, C.S. (South African Journal of Enology and Viticulture, 2017)
Juice filtrates of grape samples of the cultivars Cape Riesling, Chenin blanc and Colombar from different wine regions of South Africa, were fermented under standardised anaerobic conditions at a temperature of 15°C. Juice clarification reduced fermentation rates but marked differences between the cultivars were observed. Whereas most of the Cape Riesling filtrates fermented dry at a moderate rate, fermentation of the Colombar juice filtrates were strongly retarded or lagged. The Chenin blanc juices fermented at a rate intermediate to these two. It was established that all slow fermentations were caused by nutritional deficiencies of the juices as a result of filtration and that fermentation could be restored to normal by addition of combinations of er osterol and unsaturated fatty acids.